(untitled) - Kinicki, Angelo (Boston, 2006)
In addition to facilitating active learning, "Organizational Behavior: Key Concepts, Skills & Best Practices" meets the needs of those instructors looking for a brief, paperback text for their OB course, who do not want to sacrifice content or pedagogy. This book provides lean and efficient coverage of topics such as diversity in organizations, ethics, and globalization, which are recommended by the Association to Advance Collegiate Schools of Business (AACSB). Timely chapter-opening vignettes, interactive exercises integrated into each chapter, four-color presentation, lively writing style, captioned color photos, cartoons, and real-world in-text examples make "Organizational Behavior: Key Concepts, Skills & Best Practices" the right choice for today's business/management student. The topical flow of this 16-chapter text goes from micro (individuals) to macro (groups, teams, and organizations). Mixing and matching chapters and topics within chapters in various combinations is possible and encouraged to create optimum teaching/learning experiences.
Keywords: Organizational behavior